HISTORY OF THE CATERING SYSTEM IN UZBEKISTAN: CHANGES, PLANS AND PRACTICE (LATE XIX - EARLY XX CENTURIES) - Nasirov, Bunyod (Science technology&Digital finance, 2023)
In the article, the author describes the changes in the catering system in the late 19th and early 20th centuries, the emergence and development of new types of service in the industry, and the reaction of the population to these changes.